Becoming the state-funded madrasah or retaining autonomy: the case of two madrasahs in Kelantan - Latief, Hilman; Robani, Anidah; Ahamat, Amiruddin; Rozikan (STAIN Kudus, 2021)
Malaysia witnessed the rise of Islamic education more than a century ago, partly evidenced by the establishment of traditional Islamic education institutions called pondok or madrasah. Starting in the nineteenth century, Islamic pondok schools spread in Malaysia, founded by 'ulama (Islamic scholars) who gained financial support from the community. As time went by, many pondok, previously supported by civil society, began to face financial difficulties because of the changing political landscape, economic situation, the death of their founders, and changes in government policy. This paper investigates the experiences of two madrasahs in the state of Kelantan in Malaysia and the strategies they have adopted to resolve their financial issues. This paper argues decisions and strategies regarding financing were influenced by several factors, including the degree of attachment felt by the current asatidz (teachers) to the history of their pondok, their desire to preserve the legacy of the madrasah founder, and the level of economic pressure they experienced. The primary choice was between relinquishing ownership to the state by becoming a state (funded) school or remaining a self-governed school with limited access to state funds.